THE DEVELOPMENT OF MARITAL RAPE IN ISLAMIC FAMILY LAW REFORM - Sya’ima, Arwa; Widiyanto, Widiyanto; Alotaiby, Nemer (JURNAL ILMU SYARIAH, 2024)
Marriage is a sacred bond that governs the relationship between husband and wife based on love, affection, and mutual respect. However, in practice, domestic violence often occurs, one of which is sexual violence in the form of marital rape. This research aims to examine the development of understanding of marital rape in the context of Islamic family law reform. This research uses a qualitative method with a normative juridical approach, utilizing data from literature, books, journals, and relevant articles. The research results show that changes in Islamic family law regarding marital rape through a moderate Islamic legal perspective, which is responsive to the times, can support the eradication of sexual violence within marriage. In addition, legal developments in Indonesia are now beginning to recognize marital rape as a criminal offense, providing stronger protection for victims. This research is expected to contribute to strengthening legal and social awareness regarding the importance of justice and protection for women in domestic life.